Higher mortality and longer length of stay in hospitalized patients with newly diagnosed diabetes - Jang, Seol A; Min Kim, Kyoung; Jin Kang, Hye; Heo, Seok-Jae; Sik Kim, Chul; Won Park, Seok (Diabetes research and clinical practice, 2024)
We investigated the association between diabetes status at admission and in-hospital outcomes in all hospitalized patients, regardless of the reason for admission. All individuals aged 20 years or older who were admitted to Yongin Severance Hospital between March 2020 and February 2022 were included in study. Subjects were categorized into three groups: non-DM, known DM, and newly diagnosed DM, based on medical history, anti-diabetic medications use, and laboratory test. Hospitalization-related outcomes, including in-hospital mortality and length of hospital stay, were compared between groups. 33,166 participants were enrolled. At hospitalization, 6,572 (19.8 %) subjects were classified as known DM, and another 2,634 (7.9 %) subjects were classified as newly diagnosed DM. In-hospital mortality was highest in newly diagnosed DM (HR 1.89, 95% CI 1.58–2.26, p < 0.001) followed by known DM (HR 1.41, 95% CI 1.18–1.69, p < 0.001) compared to non-DM. Length of hospital stay was significantly longer in newly diagnosed DM (median [IQR] 9.0 [5.0–18.0],days) than known DM (median [IQR] 5.0 [3.0–10.0],days)(p < 0.001) and non-DM (median [IQR] 4.0 [2.0–7.0],days). After adjusting for multiple covariates, newly diagnosed diabetes was independently associated with increased in-hospital mortality (p < 0.001). Diabetes status at admission was closely linked to hospitalization-related outcomes. Notably, individuals with newly diagnosed diabetes demonstrated a higher risk of in-hospital mortality and a prolonged length of hospital stay.